Hepatitis E: prevention and treatment. Issue 5 (October 2016) - Nelson, Kenrad E.; Heaney, Christopher D.; Labrique, Alain B.; Kmush, Brittany L.; Krain, Lisa J.
Abstract : Purpose of review: Infection with the hepatitis E virus (HEV) is very common worldwide. The epidemiology, viral genotypes, and transmission routes differ between low-resource countries and economically developed countries. These differences have resulted in the design of diverse prevention and treatment strategies to combat HEV. Recent findings: The population seroprevalence of HEV immunoglobulin G varies between 5 and 50%. However, the diagnosis of acute hepatitis from HEV has not been common in the United States or Western Europe. Chronic progressive HEV infections have been reported among patients who are immunocompromised. Successful treatment of patients with chronic hepatitis from HEV infection with antiviral agents, such as ribavirin or interferon-α, has been reported. Extrahepatic manifestations of HEV infection are common. Large epidemics of hundreds or thousands of cases continue to be reported among populations in Asia and Africa. A subunit peptide HEV vaccine has been found to be highly efficacious in a large clinical trial. However, the vaccine has not been evaluated in populations of pregnant women or other risk groups and is only available in China. Summary: Although HEV infections are increasingly recognized as a global public health problem, there are few methods for prevention and treatment that are widely available.